Evaluation of a randomized nutrition intervention combining nutrition education and cooking workshops on dietary intakes and psychosocial determinants of performance in university football athletes - David Larose; Shirin Panahi; Raphaëlle Jacob; Vicky Drapeau (Canadian Science Publishing, 2022)
Although nutrition influences performance, many athletes, including football players, do not meet nutritional requirements for their sport. The objective of this study was to determine the impact of a nutrition intervention combining nutrition education and cooking workshops on nutrition knowledge, intention, and perceived behavioral control in the preparation of healthy meals, dietary intakes, and diet quality in male university football players. Athletes (n = 23; age: 22 ± 1 year) were randomly assigned to an intervention (2 h/week) (n = 13) or control group (n = 10) over three weeks. Questionnaires were completed before (pre), immediately after (post 1), and two months after the intervention (post 2). Dietary intakes and diet quality were evaluated from three web-based 24-h dietary recalls per visit. Mixed linear models for repeated measures with Tukey's post hoc test were performed to determine the effects of the intervention on all outcomes. There was a group by time interaction for nutrition knowledge (p = 0.002) that was higher immediately after and two months after the intervention compared to the control group. No differences on other outcomes were observed. Combining nutrition education and cooking workshops improved nutrition knowledge, but did not affect intention and perceived behavioral control in the preparation of healthy meals, dietary intakes, and diet quality in male university football athletes.